Pengendalian Risiko Pembiayaan pada Lembaga Keuangan Mikro Syariah menggunakan Enterprise Risk Management (ERM): Studi Kasus di Indonesia - Cut dina atika; Achmad Firdaus; Mukhamad Yasid (IRTIQO' : Postgraduate Journal of Islamic Economics, Finance and Accounting Studies, 2022)
The purpose of research is to analyze the risks of Islamic Micro Finance. Islamic finance calculate potential losses, financial risk assessment and risk mitigation. By using Creditrisk+ with software Minitab 16 and Microsoft Excel. Data used in this research is financial statements of Islamic Cooperatives in Indonesia in 2015-2017. The sharia financing risk was analized with ERM framework and creditrisk+ method. The result showed that the highest risk of sharia financing is customer’s default due to their bad character or moral hazard. The possible risk mitigation actions are resceduling, restructuring and withdrawing customers' collateral.